PENGARUH LAJU ALIR UDARA DAN WAKTU PROSES GASIFIKASI TERHADAP GAS PRODUCER LIMBAH TANGKAI DAUN TEMBAKAU MENGGUNAKAN GASIFIER TIPE DOWNDRAFT - Suhendi, Endang; Paradise, Gilang Umar; Priandana, Idham (Jurnal Bahan Alam Terbarukan, 2016)
The continued development of industry and agriculture along with unutilized of industrial and agricultural wastes properly, the waste will only be garbage which can be an interference to environment. Is required to have waste treatment technologies that are effective, efficient and environmentally friendly to utilize the waste into renewable energy sources. The way of handling this waste is to use gasification technology. Gasification is a method of thermochemical conversion of solid fuels into the syngas gas fuel in the gasifier container by supplying a gasification agent such as steam, air and others. The purpose of this research is to determine the effect of air flow rate and the time of gasification process for tobacco leaf stalkâs waste againts to the composition and the components of syngas. This research is conducted using a gasifier with a capacity of Â± 2.5 kg. The research procedures are drying, crushing, sizing, gasification process, and analysis of gas compositions. The result of this research has proven that tobacco leaf stalkâs waste has potential to be renewable energy sources which can produce syngas using gasification process. The concentration of syngas (CO, H2 and CH4) which is the highest obtained at variation of Q = 3 m3 / h in minutes 30 with syngas concentration of 2.27% vol CH4, CO gas amounted to 7.17% vol and H2 gas amounted to 5.79 % vol.